The Religious life of Romanians in 18th-20th century Hungary, reflected in the works of researchers in the Hungarian space - Scridon, Alin Cristian (Journal of Education Culture and Society, 2020)
Aim. We tend to believe that the religious life of Romanians in the diaspora – living in the proximity of the Romanian borders (we do not take into account the groups that left towards Spain, Italy, Germany, and so on at the beginning of the third millennium) - is a taboo subject. The Orthodox (Romanian) clerical elite focused less on the assiduous study of the religious life of their Romanian brothers outside the borders; in this case, in Hungary. Therefore, we have the scientific duty—but more importantly, the moral duty—to bring to light the truths that are either not known or are known in a distorted form. The road of Voniga (Giula-Giroc) that we followed during the PhD research period was a blessing from the point of view of a scientific void/niche. Methods. In our study, we have applied two “simple” components: the archive and the specialised bibliography. Results. The archive was largely preserved only by Elena Csobai and Emilia Martin. The respectable ladies professionally structured the archive (Romanian Orthodox Church in Hungary) and saved hundreds of research sources from the depth of history. Conclusion. As Moisa noted (2011), the puzzling ethnographic, linguistic, cultural, and historical bulk material is without a doubt focused on the Church. The church is inextricably linked to the lives of Romanians in Hungary. Going through the tens of thousands from the mentioned fields, even superficially, there is an undeniable truth: the spirituality is present, more or less, in the writings of most of the select researchers who have worked in the scientific field for the past three decades.